AIR REBUSAN CENGKEH UNTUK MENGURANGI FREKUENSI MUAL DAN MUNTAH PADA IBU HAMIL TRIMESTER AWAL - Nurmaliza, Nurmaliza; Yusmaharani, Yusmaharani; Ratih, Rini Hariani (MIDWIFERY JOURNAL, 2021)
Background : Pregnancy is a physiological and natural process. The process of pregnancy can affect the condition of the body as a whole, such as the occurrence of physiological changes in organ systems, changes that occur in pregnant women due to an imbalance in the work of the hormones estrogen and progestergen. This imbalance produces placental HCG or (Human Chorionic Gonadotropine) which causes pregnant women to feel nausea and vomiting. In Primigravida nausea and vomiting occurs in 60-80% of pregnant women and 40-60% occurs in multigravida. This is due to differences in hormonal changes in each pregnant woman so that not all pregnant women experience nausea and vomiting. Nausea experienced during pregnancy can be overcome by using complementary therapies with easily available ingredients such as cloves. The content of astringent oil in cloves can overcome digestive problems such as nausea and vomiting.Purpose : The purpose of this study was to determine the effect of clove boiled water to reduce the frequency of nausea and vomiting in early trimester pregnant women at BPM Siti Juleha.Methode : The research design used is a pre-experiment which is one group pretest-posttest. The population in this study were pregnant women in the 1st trimester or early trimester, the samples were taken using a purposive sampling technique, namely taking samples only according to the research criteria such as experiencing nausea and vomiting more than 3 times a day, pregnant in the early trimester, not taking anti-nausea drugs with the number of samples as many as 32 pregnant women. To see the effect of giving clove water with reducing the frequency of nausea and vomiting, Bivariate analysis was used with paired t-test.Result : The results of this study indicate that there is a change in the frequency of vomiting malpractices of respondents who before the intervention experienced nausea and vomiting on average 7 times a day, after being given the clove boiled water intervention the average frequency of nausea and vomiting decreased to 3.8 times a day with a value of 3.8 times a day. Pvalue = 0.000. The results of this study can be concluded that clove boiled water has an effect on reducing the frequency of nausea and vomiting in early trimester pregnant women.Conclusion : There is an effect of giving cloves boiled water to reduce the frequency of nausea and vomiting in early trimester pregnant women at BPM Stiti Juleha with P value = 0.000. The researcher hopes that respondents can increase their knowledge about the benefits of clove boiled water to reduce complaints of nausea and vomiting in early pregnancy. Kata Kunci : clove Boiled, nauseous and vomit, pregnant in the early trimester  ABSTRAK Latar Belakang : Masa Kehamilan adalah suatu proses yang fisiologis dan alamiah. Proses kehamilan dapat mempengaruhi kondisi tubuh secara keseluruhan seperti terjadinya perubahan fisiologis pada sistem organ, perubahan yang terjadi pada perempuan hamil karena ketidakseimbangan kerja hormon estrogen dan progestrogen. Ketidakseimbangan ini menghasilkan HCG plasenta atau (Human Chorionic Gonadotropine) yang menyebabakan Wanita hamil merasakan mual dan muntah. Pada Primigravida mual muntah terjadi pada 60 – 80 % ibu hamil dan 40 – 60 % terjadi pada multigravida. Hal ini disebabkan perbedaan perubahan hormon pada setiap perempuan hamil sehingga tidak semua perempuan hamil mengalami mual dan muntah. Rasa mual yang dialami selama kehamilan bisa diatasi dengan menggunakan terapi komplementer dengan bahan yang mudah didapatkan seperti cengkeh, Kandungan minyak astrisi pada cengkeh dapat mengatasi masalah pencernaan seperti mual dan muntah.Tujuan  : Tujuan penelitian ini adaah untuk mengetahui pengaruh air rebusan cengkeh untuk mengurangi frekuensi mual dan muntah pad ibu hamil trimester awal di BPM Siti Juleha.Metode : Design penelitian yang digunakan adalah Pra-eksperimen yang bersifat one grup pretest-postest. Populasi pada penelitian ini adalah ibu hamil trimester 1 atau trimester awal, sampel yang diambil menggunakan Teknik purposive sampling yaitu mengambil sampe hanya sesuai kriteria penelitian seperti mengalami mual dan muntah lebih dari 3 kali dalam sehari, hamil trimester awal, tidak sedang mengkonsumsi obat anti mual dengan jumlah sampel sebanyak 32 orang ibu hamil. Untuk melihat pengaruh pemberian air cengkeh denganpengurangan frekuensi mual dan muntah menggunakan analisis Bivariat yang dilakukan dengan uji paired t-test.Hasil : Hasil penelitian ini menunjukkan adanya perubahan frekuensi mal muntah responden yang sebelum diberikan intervensi rata-rata responden mengalami mual dan muntah sebanyak 7 kali sehari, setelah diberikan intervensi air rebusan cengkeh rata-rata frekuensi mual dan muntah menurun menjadi 3,8 kali dalam sehari dengan nilai P= 0,000. Hasil penelitian ini dapat disimpulkan bahwa air rebusan cengkeh memberikan pengaruh terhadap penurunan frekuensi mual dan muntah pada ibu hamil trimester awal.Kesimpulan : Terdapat pengaruh pemberian air rebusan cengkeh terhadap penurunan frekuensi mual dan muntah ibu hamil trimester awal di BPM Stiti Juleha dengan nilai P=0,000. Harapan peneliti yaitu agar responden dapat menambah pengetahuannya tentang manfaat air rebusan cengkeh untuk mengurangi keluhan mual dan muntah pada awal kehamilan. Kata Kunci : Air Rebusan Cengkeh, Mual dan Muntah, Hamil Trimester Awal